Estudo de métodos cromatográficos, eletroforético e biológicos in vitro para análise de rivaroxabana - Walter, Maurício Elesbão (2019)
Rivaroxaban (RIV) is an oral anticoagulant with the mechanism of action based on the inhibition of the factor Xa of the coagulation cascade. It is clinically used for the prophylaxis and treatment of thromboembolic diseases and nonvalvular atrial fibrillation. In the present research, a stability-indicating micellar electrokinetic capillary chromatography (MEKC) method was validated for the analysis of RIV in tablets dosage forms, and the results were compared to those of the anti-factor Xa bioassay and the reversed-phase high performance liquid chromatography (RP-HPLC) method. Besides, the chiral-HPLC was optimized to separate the enantiomers. The MEKC method was performed on a fused-silica capillary (effective length 40 cm and 50 μm i.d.), maintained at 25ºC, and the separation voltage was 30 kV. The background electrolyte solution consisted of 75 mM MES buffer and 25 mM sodium dodecyl sulphate (SDS) solution at pH 2.0. Injections were carried out using a pressure mode at 50 mbar for 60 s, with detection by a photodiode array detector set at 202 nm. The migration time was 2.81 min and the method was linear over the concentration range of 0.5 – 50 μg/mL (r² = 0.9991). The detection limit (DL) and quantitation limit (QL) were 0.16 μg/mL and 0.54 μg/mL, respectively. Specificity and stability-indicating capability of the method were established in degradation studies, which also showed that there was no interference of the excipients. The accuracy was 100.67% with bias lower than 1.60%. The proposed method was applied to the quantitative analysis of RIV in tablet dosage forms and the results were correlated to those of the anti-factor Xa assay and the validated RP–HPLC method showing values 0.66% higher and 0.59% lower, respectively, with non-significant differences (p > 0.05). The results show that the MEKC could constitute an alternative for the analysis of the tablets. Then, the chiral-HPLC was performed to separate the enantiomers, which were subjected to the anti-factor Xa assay and cytotoxicity test, showing low activity for the R-enantiomer and lower toxicity. The results of the physicochemical methods were compared to those of the anti-factor Xa assay, which showed non-significant differences (p > 0.05). Besides, the analytical capability of each method was emphasized, and only the chiral RP-HPLC was able to detect and quantify the enantiomeric forms. In this context, the present research represents a contribution to guarantee the quality, to assure the safety and therapeutic efficacy of the pharmaceutical products, and to establish bases for advances in the study of the generic drug containing RIV.